Survival comparison of breast conserving therapy and mastectomy with breast reconstruction for breast cancer using propensity score matched cohort - Hao Li; Shen Tian; Juan Wu; Shu Li; Jun Xiao; Yu-ling Chen; Jing-yu Song; Qin Pan; Xin-yu Liang; Rui-ling She; Chen-yu Ma; Kai-nan Wu; et al. (Scientific Reports)
Abstract Cohort studies have suggested that breast-conserving therapy (BCT) offers better survival outcomes compared to mastectomy in patients with early breast cancer (BC). However, survival comparisons between BCT and mastectomy with breast reconstruction (Mastectomy + BR) are lacking. To investigate this, we conducted a cohort study using data from the SEER database. Patients with first-diagnosed locoregional BC between 2010 and 2016 were included and categorized into BCT and Mastectomy + BR groups. Propensity score matching (PSM) was performed to reduce selection bias. Breast cancer-specific survival (BCSS) and overall survival (OS) were compared between the groups. After PSM, 56,420 patients were matched (1:1) into the BCT and Mastectomy + BR groups. No significant differences in BCSS or OS were observed between the two matched groups overall. However, subgroup analyses based on tumor size and nodal status showed that, among patients with node-negative and tumors ≤ 5 cm, Mastectomy + BR was associated with decreased BCSS compared to BCT (HR 1.23, 95% CI 1.02–1.49, P = 0.03). Inferior BCSS for Mastectomy + BR was also observed in tumors located in the upper-outer quadrant (HR  1.54, 95% CI 1.07–2.20, P = 0.02), nipple & central area (HR 4.98, 95% CI 1.44–17.21, P = 0.01), and in triple-negative BC (HR  1.45, 95% CI 1.07–1.98, P = 0.02). Additionally, in triple-negative BC, Mastectomy + BR was associated with worse OS (HR  1.33, 95% CI 1.00–1.76, P = 0.048). For patients with node-positive or tumors > 5 cm, no significant differences in BCSS or OS were found between the BCT and Mastectomy + BR groups, except in the HER2-enriched subtype, where Mastectomy + BR was associated with improved BCSS (HR 0.43, 95% CI 0.22–0.85, P = 0.015) and a marginal better OS (HR 0.54, 95% CI 0.29–1.01, P = 0.055). This study suggests that, except for the HER2-enriched subtype, BCT remains an equivalent or, in specific clinical scenarios, a superior alternative to Mastectomy + BR for the treatment of breast cancer.